L’évaluation de l’oral dans une classe de FLE au secondaire qualifiant - Sara Yassine (مجلة عطاء للدراسات والأبحاث)
The teaching of foreign languages has mainly been based on the written word, thus eclipsing the primary manifestation of language, i.e. the spoken word. This is reflected in the way oral language is assessed in Moroccan classrooms. At the opposite end of the spectrum from the written word, oral expression is ephemeral, spontaneous and irreversible. The teacher is therefore faced with the task of evaluating an activity that is fluctuating, variable and protean. What's more, since it doesn't fit into the official assessment slots, oral expression is subject to an approximate, global assessment. A study of the various components of oral expression is necessary to provide a basis for approaches to its evaluation. Three approaches will therefore be used to establish the modalities for putting oral assessment into practice.